Commercio internazionale e glpbalizzazione delle economie nelle tematiche della Rivista di Studi politici internazionali - Tosato, Domenico (Rivista di studi politici internazionali, 2007)
The present paper offers an enlarged version of a text read on the occasion of the Round Table presentation of the New Series of the Rivista di Studi Politici Internazionali. The aim of the paper is to present a critical evaluation of the problems posed by the extraordinary increase in the trade flows, in direct foreign investment and financial capital movements that characterisesthe present phase of the international relations among the industrialisedCountries of the Western World, the developing Countries and the newly industrialised Countries of the Far East. In line with the main findings of economic theory, the paper shares the idea that international trade is beneficial to all trading partners, in as much as it leads to a more efficient resource allocation. The available empirical data support this conclusion. The paper highlights, however, the problems of income distribution and unbalanced growth that may result from trade and links these problems to the present situation of the advanced Countries, that are facing the threat of exports fromlow labour cost competitors. In this specific context the problem of international sourcing of manufacturing components and services is exa ined and the possible effects on the economies of the advance Countries considered. The need for a better coordination of trade policy, especially in the field of financialcapital movements, is underlined in order to make the movement toward globalisation more beneficial to and better accepted by all Countries. Ce papier offre une version élargie du texte qui a été lu lors de la présentation de la Nouvelle Série de la Rivista di Studi Politici Internazionali. L’Auteur y examine d’un oeil critique les problèmes posés par l’augmentation extraordinaire du commerce international, des investissements directs étrangers,des mouvements des capitaux financiers, qui caractérise aujourd’hui, au point de vue économique, les relations internationales entre les Pays industrialisés de l’Occident, les Pays en voie de développement et les Pays nouvellementindustrialisés de l’Extrême-Orient. Basé sur les conclusions les plus convaincantes auxquelles la théorie économique est arrivée, ce papier partage l’idée que le commerce international est bénéfique pour tous les partners commerciaux, en tant que ceci conduit à une meilleure affectation des ressources. Lesdonnées empiriques disponibles appuyent cette thèse. Le papier souligne, cependant, les problèmes de distribution du revenu et de croissance instable qui peuvent résulter du commerce et lie ces problèmes à l’état où se trouvent aujourd’hui les Pays avancés face à la menace d’exportations de concurrents pour lesquels le coût du travail est bas. Dans ce contexte spécifique l’A. examine le problème du sourcing international des composants de fabrication et des services et les effets qui peuvent en résulter sur les économies des Pays avancés. L’A. souligne le besoin d’une politique commerciale mieux coordonnée spécialement en ce qui concerne les mouvements des capitaux financiers, afin de rendre le mouvement vers la mondialisation plus bénéfique pour et mieux accepté par tous les Pays.